Supervision and Control in Euthanasia Law: Going Dutch? - Adams, Maurice; Weyers, Heleen (Revista Direitos Humanos Fundamentais, 2013)
How can one encourage physicians to subject the practice of euthanasia to external supervision and control? This is the task inevitably facing any government that comes to the conclusion that traditional means of protecting life via a strict criminal prohibition of euthanasia do not stop doctors from ending life.In this article we will deal with how the respective Dutch and Belgian governments dealt with this task: how are the supervision and control systems for euthanasia organised, how do they function, and how are after-the-fact and before-the-fact supervision and control related to each other? The focus will mainly be on the situation in the Netherlands (on which the Belgian situation is modelled), with the Belgian situation presented as contrasting material.